Analisis Target Pemasaran Menggunakan Algoritma K-Means Clustering (Studi Kasus: Hotel Sutan Raja Soreang) - Romiwita Irene Klarita; Fergie Joanda Kaunang (TeIKa, 2020)
Sutan Raja Hotel and Convention Center Soreang conducted a marketing technique by sending a random marketing team to do a promotion. The marketing team sent randomly may not be able to achieve the expected target. In order to achieve the target, the placement of the appropriate marketing team will get more efficient results. Customer data that has been stored when a customer registers for check-in at Sutan Raja Hotel and Soreang Convention Center, can be utilized to create marketing support strategies that can be very useful for the Hotel. Data used in marketing strategy decision support include data from the customer's home city, gender, main segment, and duration of stay that is analyzed using the K-Means Clustering Algorithm so that the right customer cluster is known for the promotion approach. Data will be processed using Weka data processing software with K-Means Clustering Algorithm and K = 3 so that the data will produce three clusters. With the final result of Cluster 0 in Jakarta City, male gender, OTA segment play, and 1 day stay duration. Cluster 1, Jakarta City, male gender, individual segment play, and duration of stay for 3 days. Cluster 2 Bandung City, male gender, individual segment play, and duration of stay of 2 days.